Malignant Pure Pulmonary Ground-Glass Opacity Nodules: Prognostic Implications - Park, Jong Heon (The Korean Society of Radiology, 2009)
OBJECTIVE: This study was designed to evaluate follow-up results in terms of patient prognosis for malignant pulmonary nodules depicted as pure ground-glass opacity (GGO) lesion observed at high-resolution CT (HRCT). MATERIALS AND METHODS: Surgical removal for malignant GGO nodules was accomplished in 58 patients (26 men, 32 women; mean age, 57 years; age range, 29-78 years). Patient prognoses were assessed by patient clinical status and the presence of changes in nodule size determined after a follow-up HRCT examination. Differences in patient prognoses were compared for nodule number, size, surgical method, change in size before surgical removal, and histopathological diagnosis by use of Fisher's exact test and Pearson's chi-squared test. RESULTS: Of the 58 patients, 40 patients (69%) were confirmed to have a bronchioloalveolar carcinoma (BAC) and 18 patients (31%) were confirmed to have an adenocarcinoma with a predominant BAC component. Irrespective of nodule size, number, treatment method, change in size before surgical removal and histopathological diagnosis, neither local recurrence nor a metastasis occurred in any of these patients as determined at a follow-up period of 24 months (range; 12-65 months). Of 14 patients with multiple GGO nodules, all of the nodules were resected without recurrence in six patients. In the remaining eight patients, the remaining nodules showed no change in size in seven cases and a decrease in size in one case as determined after a follow-up CT examination. CONCLUSION: Prognoses in patients with pure GGO malignant pulmonary nodules are excellent, and not significantly different in terms of nodule number, size, surgical method, presence of size change before surgical removal and histopathological diagnosis.